Silicon nitride powder and resin composition using same

By optimizing the shape, strength, density, and grain boundary properties of silicon nitride powder, the problem of insufficient thermal diffusivity in the resin composition was solved, achieving efficient thermal diffusion and conduction, which is suitable for heat dissipation of highly integrated electronic devices and high-current driven electronic components.

CN120957944APending Publication Date: 2025-11-14SUMITOMO CHEM CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480022616.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-31
Filing Date
2024-02-21
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

In the prior art, when silicon nitride powder is used as a filler in resin compositions, its thermal diffusivity has not yet reached its optimal level, making it difficult to meet the heat dissipation requirements of highly integrated electronic devices and high-current driven electronic components.

Method used

A silicon nitride powder is provided, which improves thermal diffusivity by controlling the shape, strength, density, β-saturation and grain boundary characteristics of its particles to ensure that it is not easily destroyed in a resin composition.

Benefits of technology

By optimizing the properties of silicon nitride powder, the thermal diffusivity and thermal conductivity of the resin composition are significantly improved, making it suitable for high-efficiency heat dissipation materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120957944A_ABST
    Figure CN120957944A_ABST
Patent Text Reader

Abstract

One purpose of the present invention is to provide a silicon nitride powder which is used as a filler for a resin composition and which is capable of improving the thermal diffusivity of the resin composition. The present invention relates to a silicon nitride powder comprising a plurality of silicon nitride particles, the silicon nitride particles satisfying at least one selected from the group consisting of (i) and (ii) in a particle compression test. (i) The ratio of the displacement of the breaking point to the maximum displacement exceeds 0.22. (ii) The strength at the maximum displacement exceeds 3473 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a silicon nitride powder and a resin composition using the silicon nitride powder. Background Technology

[0002] The heat generated by electronic components when powered on is dissipated through a heat sink. To improve heat dissipation efficiency, a technique is known to fill the space between the electronic components and the heat sink with a heat-dissipating material.

[0003] As a heat dissipation material, resin compositions containing resin and inorganic particles are known, and silicon nitride powder (e.g., Patent Document 1) can be used as the inorganic particles.

[0004] Patent Document 1 discloses a low-aluminum spherical β-silicon nitride powder used as a filler in electronic packaging materials. This silicon nitride powder is characterized by a sphericity of 0.5 to 0.99, an Al impurity content of less than 500 ppm, and a particle size range of 0.5 μm to 50 μm.

[0005] Patent Document 2 discloses a method for manufacturing silicon nitride powder suitable for producing silicon nitride sintered bodies, and the silicon nitride powder obtained by the method. The silicon nitride powder has an average particle size of 1 to 50 μm, a metal oxide content of 0 to 10 wt%, and an impurity content of less than 1 wt%. Preferably, the metal oxide content in the silicon nitride powder is less than 1 wt%. The resulting sintered body has a thermal conductivity of 90 W / mK or higher and a flexural strength of 700 MPa or higher. The preferred sintering conditions for the sintered body are as follows: mixing the silicon nitride powder with MgO and Y2O3 and grinding them, dry pressing the blank into shape, and then sintering the blank under gas pressure at 1900°C and 1 MPa nitrogen pressure for 8 hours.

[0006] Patent document 3 discloses a silicon nitride powder suitable for manufacturing high thermal conductivity silicon nitride sintered bodies. The silicon nitride powder is characterized by comprising columnar particles with a β fraction of 30-100%, an oxygen content of less than 0.5 wt%, an average particle size of 0.2-10 μm, an aspect ratio of less than 10, and grooves formed along the long axis of the particles.

[0007] Existing technical documents

[0008] Patent documents

[0009] Patent documents Japanese Patent Publication No. 2022-522814

[0010] Patent documents Japanese Patent Publication No. 2022-541208

[0011] Patent documents Japanese Patent Application Publication No. 2004-262756 Summary of the Invention

[0012] In recent years, the increased heat generation in ICs due to their high integration, and the increased heat generation in electronic components due to the use of high-current driven electronic components in electric vehicles, aircraft, and other electric vehicles have become problems. To achieve more effective heat dissipation, it is necessary to further improve the thermal diffusivity of resin compositions.

[0013] In Patent Document 1, by increasing the sphericity of silicon nitride powder (i.e., making it into spherical particles), it is possible to highly fill the resin composition, thereby improving the thermal diffusivity of the resin composition. However, further research is needed to further improve the thermal diffusivity.

[0014] The silicon nitride powder disclosed in Patent Documents 2-3 is silicon nitride powder used for silicon nitride sintered bodies, therefore no research has been conducted on silicon nitride powder that is mixed with resin to form a resin composition and as a filler suitable for the resin composition.

[0015] In view of this, an objective of embodiments of the present invention is to provide a silicon nitride powder used as a filler in a resin composition, specifically a silicon nitride powder capable of improving the thermal diffusivity of the resin composition. Furthermore, another objective of embodiments of the present invention is to provide a resin composition using silicon nitride powder.

[0016] Method 1 of the present invention is a silicon nitride powder comprising a plurality of silicon nitride particles, wherein, in a particle compression test, the ratio of the displacement of the failure point to the maximum displacement exceeds 0.22.

[0017] The second embodiment of the present invention is silicon nitride powder according to embodiment 1, wherein the silicon nitride particles have a destructive strength of more than 727 MPa in the compression test of the particles.

[0018] Embodiment 3 of the present invention is silicon nitride powder according to Embodiment 1 or 2, wherein the apparent density exceeds 3.17 g / cm³. 3 .

[0019] The fourth embodiment of the present invention is silicon nitride powder according to any one of embodiments 1 to 3, wherein the β-saturation is 65% or more.

[0020] The fifth embodiment of the present invention is a silicon nitride powder according to any one of embodiments 1 to 4, wherein the maximum particle size of the silicon nitride particles is 6.8 μm or more, wherein the ratio (L2 / L1) of the total length L2 of the inner boundary lines to the length L1 of the outer edge is 1% or less.

[0021] The sixth embodiment of the present invention is silicon nitride powder according to any one of embodiments 1 to 5, wherein the silicon nitride particles have a strength at the maximum displacement exceeding 3473 MPa in the compression test of the particles.

[0022] The seventh embodiment of the present invention is silicon nitride powder according to any one of embodiments 1 to 6, wherein, in the compression test of the silicon nitride particles, the ratio of the breaking strength to the strength at the maximum displacement is 0.18 or more.

[0023] The 8th embodiment of the present invention is silicon nitride powder according to any one of embodiments 1 to 7, wherein the following formula (1) is satisfied.

[0024] (|a-23.34| / 23.34+|b-27.01| / 27.01+|c-33.63| / 33.63+|d-36.02| / 36.02) / 4<0.292 •••(1)

[0025] In equation (1), a, b, c and d are the diffraction angles 2θ (°) corresponding to the (110), (200), (101) and (210) planes of β-type silicon nitride in the X-ray diffraction pattern with CuKα rays as the X-ray source.

[0026] The present invention provides a silicon nitride powder comprising a plurality of silicon nitride particles, wherein the strength of the silicon nitride particles at the maximum displacement exceeds 3473 MPa in a particle compression test.

[0027] The present invention, embodiment 10, is based on the silicon nitride powder of embodiment 9, wherein the ratio of the breaking strength to the strength at the maximum displacement of the silicon nitride particles in the compression test of the particles is 0.18 or more.

[0028] The present invention, in embodiment 11, is silicon nitride powder according to embodiment 9 or 10, wherein the following formula (1) is satisfied.

[0029] (|a-23.34| / 23.34+|b-27.01| / 27.01+|c-33.63| / 33.63+|d-36.02| / 36.02) / 4<0.292 •••(1)

[0030] In equation (1), a, b, c and d are the diffraction angles 2θ (°) corresponding to the (110), (200), (101) and (210) planes of β-type silicon nitride in the X-ray diffraction pattern with CuKα rays as the X-ray source.

[0031] Embodiment 12 of the present invention is silicon nitride powder according to any one of embodiments 9 to 11, wherein the apparent density exceeds 3.17 g / cm³.3 .

[0032] The present invention, embodiment 13, is silicon nitride powder according to any one of embodiments 9 to 12, wherein the β-saturation is 65% or more.

[0033] The present invention, embodiment 14, is a silicon nitride powder according to any one of embodiments 9 to 13, wherein the maximum particle size of the silicon nitride particles is 6.8 μm or more, wherein the ratio (L2 / L1) of the total length L2 of the inner boundary lines to the length L1 of the outer edge is 1% or less.

[0034] The present invention, embodiment 15, is silicon nitride powder according to any one of embodiments 9 to 14, wherein, in the compression test of the silicon nitride particles, the ratio of the displacement of the failure point to the maximum displacement exceeds 0.22.

[0035] The present invention, embodiment 16, is a silicon nitride powder according to any one of embodiments 9 to 15, wherein the silicon nitride particles have a destructive strength of more than 727 MPa in a compression test of the particles.

[0036] Embodiment 17 of the present invention is a resin composition comprising a resin and silicon nitride powder as described in any one of embodiments 1 to 16.

[0037] By using the silicon nitride powder according to embodiments of the present invention as a filler, a resin composition with high thermal diffusivity can be obtained. Attached Figure Description

[0038] Figure 1 This is an example of a displacement (μm) versus strength (MPa) curve obtained from a particle compression test of silicon nitride particles according to JIS R 1639-5. Detailed Implementation

[0039] [Silicon nitride powder]

[0040] In order to achieve more efficient heat dissipation, the inventors have studied silicon nitride powder as a filler in resin compositions from various perspectives. The results show that by ensuring that the silicon nitride particles in the silicon nitride powder satisfy one or more of the following (i) and (ii), for example, the silicon nitride particles are less likely to be destroyed during resin composition manufacturing, a resin composition with high thermal diffusivity can be obtained:

[0041] (i) The ratio of the displacement at the failure point to the maximum displacement exceeds 0.22;

[0042] (ii) The strength at the maximum displacement exceeds 3473 MPa.

[0043] Hereinafter, embodiments that at least satisfy (i) will be referred to as Embodiment 1 of the present invention, and embodiments that at least satisfy (ii) will be referred to as Embodiment 2 of the present invention, and their respective requirements will be described in detail. It should be noted that in this specification, "embodiments of the present invention" includes "Embodiment 1 of the present invention" and "Embodiment 2 of the present invention".

[0044] <Embodiment 1 of the present invention>

[0045] (The ratio of the displacement at the failure point to the maximum displacement)

[0046] The silicon nitride powder according to Embodiment 1 of the present invention comprises a plurality of silicon nitride particles, wherein, in a compression test of the particles, the ratio of the displacement at the point of failure to the maximum displacement (i.e., the maximum value of the displacement in the compression test of the particles) exceeds 0.22. Therefore, the silicon nitride particles are less likely to be destroyed, for example, during the manufacture of resin compositions, resulting in a resin composition with high thermal diffusivity. This ratio is preferably 0.24 or more, more preferably 0.26 or more, and particularly preferably 0.27 or more. There is no particular upper limit to this ratio; from a productivity point of view, it can be 0.60 or less, 0.50 or less, 0.40 or less, or 0.35 or less.

[0047] The ratio of the displacement of the aforementioned failure point of the silicon nitride particle to the maximum displacement was determined as follows.

[0048] First, a compression test of silicon nitride particles was conducted according to JIS R 1639-5 to obtain a displacement-test force curve. The test force on this curve was then converted into strength according to the following equation (2). Figure 1 The displacement (μm) - intensity (MPa) curve is shown.

[0049] Strength (MPa) = 2.48 × test force (N) / (π × D) 2 (2)

[0050] Here, D represents the average of the major and minor axes of the silicon nitride particles in the test subject. It should be noted that these major and minor axes can be determined by observation using an optical microscope.

[0051] exist Figure 1In the case of a region with a constant slope, the minimum displacement exceeding 0 with a constant slope is designated as the failure point P1. The region from 0 to the failure point P1 is defined as the elastic deformation region (represented by a double arrow). The ratio d1 / d2 of the displacement d1 at the failure point P1 (i.e., the maximum displacement of the elastic deformation region) to the maximum displacement d2 (i.e., the displacement at the maximum displacement point P2) is used as the aforementioned "ratio of the displacement at the failure point to the maximum displacement". It should be noted that in the case of multiple regions with constant slopes, the displacement at the starting point of the region with the largest displacement difference between the end and beginning points of the aforementioned regions is designated as the failure point P1.

[0052] (Destructive strength)

[0053] For the silicon nitride powder according to Embodiment 1 of the present invention, the silicon nitride particles preferably have a breaking strength of more than 727 MPa in the particle compression test. This makes the silicon nitride particles less prone to breakage, resulting in a resin composition with high thermal diffusivity. This breaking strength is more preferably 750 MPa or more, further preferably 800 MPa or more, and particularly preferably 850 MPa or more. There is no particular limitation on the upper limit of this breaking strength; from a productivity point of view, it can be less than 3000 MPa, less than 2750 MPa, less than 2000 MPa, or less than 1500 MPa.

[0054] The destructive strength of the silicon nitride particles was determined as follows.

[0055] The compression test of silicon nitride particles was conducted according to JIS R 1639-5, and the results were obtained. Figure 1 The curve shown is a displacement (μm) versus intensity (MPa). In this curve, the intensity at failure point P1 is taken as the failure intensity s1 (MPa).

[0056] (apparent density)

[0057] The apparent density of the silicon nitride powder involved in Embodiment 1 of the present invention is preferably greater than 3.17 g / cm³. 3 More preferably, it exceeds 3.18 g / cm³. 3 This yields silicon nitride powder containing a large number of silicon nitride particles with few internal voids, resulting in silicon nitride powder that is not easily destroyed and has high thermal diffusivity and thermal conductivity. The upper limit of the apparent density is, for example, 3.44 g / cm³. 3 It should be noted that by ensuring the apparent density is not too high, it is expected that the silicon nitride powder will not easily settle and will disperse easily when mixed with the resin. To achieve this effect, the apparent density of the silicon nitride powder is preferably 3.30 g / cm³. 3 The following is more preferably 3.25 g / cm³. 3 the following.

[0058] The apparent density of silicon nitride powder was determined by hydrometer method according to JIS R 1620:1995. At least five measurements were performed, and the average value was taken as the apparent density of the silicon nitride powder. For example, an AccuPyc 1330 (MicroMeritics) could be used for the measurement.

[0059] (β-conversion rate)

[0060] In Embodiment 1 of the present invention, the β-saturation of the silicon nitride powder is preferably 65% ​​or higher. By making the β-saturation ≥ 65%, the thermal diffusivity of the silicon nitride powder and resin composition can be improved.

[0061] The β-conversion rate is more preferably 70% or more, further preferably 80% or more, even more preferably 85% or more, and particularly preferably 90% or more.

[0062] In this specification, "β-type silicon nitride content" refers to the percentage (by volume) of β-type silicon nitride contained in the silicon nitride powder relative to the total silicon nitride.

[0063] In the calculation of β-saturation, the diffraction pattern of silicon nitride powder was obtained by powder X-ray diffraction (X-ray source: CuKα rays), and the diffraction pattern was analyzed by the Gazzara & Messier method (GP Gazzara and DPMessier, “Determination of Phase Content of Si3N4 by X-ray Diffraction Analysis”, Am. Ceram. Soc. Bull., 56[9]777-80(1977)) to calculate the β-saturation.

[0064] (Silicon nitride particles with a total inner boundary length L2 to outer edge length L1 ratio (L2 / L1) of less than 1% have a maximum particle size of 6.8 μm or more.)

[0065] In Embodiment 1 of the present invention, fewer grain boundaries and voids within the silicon nitride particles contribute to improving the thermal diffusivity of the silicon nitride particles. Therefore, as an indicator of the grain boundary content within the silicon nitride particles, the ratio (L2 / L1) of the total length L2 of the boundary lines to the length L1 of the outer edge is introduced. L1 and L2 are determined based on cross-sectional observation of the silicon nitride particles. It should be noted that here, "grain boundary" and "boundary line" refer to boundaries with a crystal orientation difference (hedge angle) exceeding 15° in the EBSD analysis results (also known as large-angle grain boundaries).

[0066] When the length of the outer edge of a silicon nitride particle is defined as L1, and the total length of the boundary lines of that silicon nitride particle is defined as L2, silicon nitride particles with a small L2 / L1 ratio can be considered silicon nitride particles with a low boundary line content. In Embodiment 1 of the present invention, silicon nitride particles with an L2 / L1 ratio of 1% or less are considered to be silicon nitride particles composed of single crystals (referred to as "single crystal particles"). Single crystal particles are not easily destroyed and have high thermal diffusivity, thus easily improving thermal diffusivity when used as fillers in resin compositions.

[0067] In Embodiment 1 of the present invention, the maximum particle size of the silicon nitride particles with an L2 / L1 ratio of 1% or less (i.e., single crystals) is preferably 6.8 μm or more, more preferably 10.0 μm or more, further preferably 15.0 μm or more, and even more preferably 25.0 μm or more. These silicon nitride particles are not easily destroyed, and when filled into the resin, they form a longer thermal conduction path, thus improving the thermal diffusivity of the resin composition. There is no particular upper limit; for example, it can be 200.0 μm or less, 100.0 μm or less, or 80.0 μm or less.

[0068] (Elastic energy absorption)

[0069] For the silicon nitride powder according to Embodiment 1 of the present invention, the silicon nitride particles preferably have an elastic deformation absorption energy (also called elastic absorption energy) of more than 490 (MPa•μm) in the particle compression test. Therefore, it is believed that the silicon nitride particles can accumulate a large amount of energy applied in the compression test, continuously maintain elasticity, and are not easily damaged. The elastic absorption energy is preferably 500 (MPa•μm) or more, particularly preferably 600 (MPa•μm) or more. There is no particular upper limit to the elastic absorption energy; from a productivity point of view, it can be 3000 (MPa•μm) or less, less than 2500 (MPa•μm), or 2000 (MPa•μm) or less.

[0070] The elastic absorption energy of the silicon nitride particles is calculated as follows.

[0071] The compression test of silicon nitride particles was conducted according to JIS R 1639-5, and the results were obtained. Figure 1 The displacement (μm) versus intensity (MPa) curve is shown. Figure 1 In this calculation, the area enclosed by the curve, the straight line with strength = 0 MPa, and the straight line with displacement = d1 (the oblique part) is used as the elastic absorbed energy (MPa•μm).

[0072] The requirements for the silicon nitride powder according to Embodiment 1 of the present invention have been described above. Hereinafter, the requirements for the silicon nitride powder according to Embodiment 2 of the present invention will be described. It should be noted that the silicon nitride powder according to Embodiment 1 of the present invention can further satisfy the requirements for the silicon nitride powder according to Embodiment 2 of the present invention, thereby further improving its properties.

[0073] <Embodiment 2 of the present invention>

[0074] (Strength at maximum displacement)

[0075] The silicon nitride powder according to Embodiment 2 of the present invention comprises a plurality of silicon nitride particles, wherein the strength of the silicon nitride particles at the point of maximum displacement exceeds 3473 MPa in a particle compression test. Therefore, the silicon nitride particles are less likely to be destroyed during processes such as resin composition manufacturing, resulting in a resin composition with high thermal diffusivity. The strength at the point of maximum displacement is preferably 3500 MPa or more, more preferably 3700 MPa or more. There is no particular upper limit to the strength at the point of maximum displacement; from a productivity point of view, it can be 20000 MPa or less, less than 15000 MPa, or 7000 MPa or less.

[0076] The strength at the maximum displacement of the silicon nitride particles was measured as follows.

[0077] The compression test of silicon nitride particles was conducted according to JIS R 1639-5, and the results were obtained. Figure 1 The curve shown is a displacement (μm) versus intensity (MPa). In this curve, the intensity at the maximum displacement point P2 is taken as the intensity s2 (MPa) at the maximum displacement.

[0078] (The ratio of the breaking strength to the strength at the maximum displacement)

[0079] For the silicon nitride powder according to Embodiment 2 of the present invention, in the compression test of the silicon nitride particles, the ratio of the breaking strength to the strength at the maximum displacement is preferably 0.18 or more. Therefore, the silicon nitride particles are less prone to breakage. This ratio is more preferably 0.20 or more, further preferably more than 0.21, even more preferably more than 0.22, and particularly preferably more than 0.22. There is no particular upper limit to this ratio; from a productivity point of view, it can be 0.60 or less, or 0.50 or less.

[0080] The ratio of the destructive strength of the silicon nitride particles to the strength at the maximum displacement was determined as follows.

[0081] The compression test of silicon nitride particles was conducted according to JIS R 1639-5, and the results were obtained. Figure 1The displacement (μm) - strength (MPa) curve is shown. Then, the ratio s1 / s2 of the strength (failure strength) s1 (MPa) at the failure point P1 to the strength s2 (MPa) at the maximum displacement point P2 is taken as the above "ratio of failure strength to strength at maximum displacement".

[0082] (The average offset of the diffraction angles corresponding to the (110), (200), (101) and (210) planes of β-type silicon nitride)

[0083] In terms of improving thermal diffusivity, it is preferable that the silicon nitride powder involved in Embodiment 2 of the present invention has less strain and defects, for example, the silicon nitride powder involved in Embodiment 2 of the present invention preferably satisfies the following formula (1).

[0084] (|a-23.34| / 23.34+|b-27.01| / 27.01+|c-33.63| / 33.63+|d-36.02| / 36.02) / 4<0.292 •••(1)

[0085] In equation (1), a, b, c and d are the diffraction angles (2θ / °) of the (110), (200), (101) and (210) (or (120)) planes of β-type silicon nitride in the X-ray diffraction pattern with CuKα rays as the X-ray source.

[0086] It should be noted that in Equation (1), “23.34”, “27.01”, “33.63” and “36.02” are the literature values ​​of the diffraction angles (2θ / °) of the (110) plane, (200) plane, (101) plane and (210) plane of β-type silicon nitride, respectively.

[0087] It can be considered that by satisfying the above equation (1), β-type silicon nitride with fewer defects and strain can be obtained, which helps to improve the thermal diffusivity. The left side of the above equation (1) is more preferably 0.290 or less, and even more preferably 0.250 or less. There is no particular limitation on the lower limit of the left side of the above equation (1). From the point of view of productivity, it can be 0.005 or more, 0.010 or more, or 0.100 or more.

[0088] It should be noted that, as described above, the X-ray diffraction pattern of silicon nitride powder can be obtained by powder X-ray diffraction (X-ray source: CuKα rays).

[0089] (apparent density)

[0090] The content is the same as that described in <Embodiment 1 of the present invention>, and therefore omitted.

[0091] (β-conversion rate)

[0092] The content is the same as that described in <Embodiment 1 of the present invention>, and therefore omitted.

[0093] (Silicon nitride particles with a total inner boundary length L2 to outer edge length L1 ratio (L2 / L1) of less than 1% have a maximum particle size of 6.8 μm or more.)

[0094] The content is the same as that described in <Embodiment 1 of the present invention>, and therefore omitted.

[0095] (Elastic energy absorption)

[0096] The content is the same as that described in <Embodiment 1 of the present invention>, and therefore omitted.

[0097] The requirements for the silicon nitride powder according to Embodiment 2 of the present invention have been described above. It should be noted that the silicon nitride powder according to Embodiment 2 of the present invention can further satisfy the requirements for the silicon nitride powder according to Embodiment 1 of the present invention described above, thereby further improving its properties.

[0098] [Method for manufacturing silicon nitride powder]

[0099] The silicon nitride powder involved in the embodiments of the present invention can be manufactured by the following method, the manufacturing method comprising:

[0100] (1) A process for synthesizing silicon nitride composite crystals by combustion synthesis under a nitrogen atmosphere using raw materials containing Si.

[0101] (2) The process of crushing silicon nitride composite crystals to obtain coarsely pulverized silicon nitride powder.

[0102] (3) The process of micronizing coarse silicon nitride powder to obtain micronized silicon nitride powder, and

[0103] (4) The process of heat-treating the micronized silicon nitride powder to obtain silicon nitride powder.

[0104] The following is a detailed description of each process.

[0105] • Process (1): The process of synthesizing silicon nitride composite crystals

[0106] As a raw material containing Si, Si powder is used, for example.

[0107] The average particle size D50 of the raw materials is, for example, in the range of 2–10 μm. This allows for the suppression of oxygen impurities while simultaneously increasing the combustion rate and synthesis temperature, resulting in good crystal growth. As an example, the average particle size D50 of Si is 5 μm.

[0108] The diluent is used to adjust the Si content in the raw material. A separately prepared silicon nitride powder is used as the diluent. This diluent can be either α-type silicon nitride powder or β-type silicon nitride powder, or they can be mixed. The average particle size D50 of the diluent is preferably in the range of 0.5 to 2.0 μm. As an example, the average particle size D50 of the diluent is 1.0 μm. The amount of diluent added relative to the total raw material (including the diluent) is set to less than 10% by mass. As an example, the diluent is added at 5 to 8% by mass relative to the total raw material. By keeping the amount of diluent added within the above range, silicon nitride powder with a specified displacement (μm) – strength (MPa) can be easily obtained.

[0109] In an embodiment of the invention, a diluent is mixed with the raw materials and then filled into a heat-insulating and heat-resistant container. The heat-insulating and heat-resistant container has a thermal conductivity of 1 W / mK or less, and can be made of alumina or zirconium oxide; carbon is preferred to account for impurities. After filling with the raw materials, the container is covered with a material of the same material as the heat-insulating and heat-resistant container. Furthermore, to increase the internal temperature of the synthesized body during combustion, the thickness of the mixed raw materials is greater than 100 mm, preferably greater than 100 mm and less than 150 mm. Combustion synthesis is carried out in a nitrogen atmosphere ranging from 0.5 to 1 MPa (e.g., 0.9 MPa). By setting the pressure range within the above range, efficient synthesis can be achieved while suppressing increases in equipment costs.

[0110] When filling the crucible with the mixed raw materials, a layer of silicon nitride powder with a thickness of 1 mm to 80 mm is laid on the bottom and sides of the crucible, and then the mixed raw materials are filled in. The top is then covered with another layer of silicon nitride powder with a thickness of 1 mm to 80 mm. The thickness of the powder coating is less than 100 mm, preferably 1 mm to 80 mm. By covering the mixed raw materials with powder, the temperature of the mixed raw materials can be maintained, and silicon nitride powder with a specified displacement (μm) – strength (MPa) can be easily obtained.

[0111] To more effectively promote crystal growth, catalysts can be used, such as adding approximately 0.01–0.1% by mass of Y₂O₃, Fe₂O₃, CaO, Ni, Co, C, etc. Additionally, external auxiliary heating in the range of 500°C–1700°C (e.g., 1500°C) can be applied, even through autogenous combustion synthesis methods, resulting in higher combustion temperatures.

[0112] • Process (2): The process of obtaining coarsely ground silicon nitride powder

[0113] Silicon nitride composite crystals are a form formed by the aggregation of multiple silicon nitride particles. In step (2), silicon nitride composite crystals can be crushed to obtain coarsely ground silicon nitride powder. For example, a general coarse crushing device such as a hammer mill or disc mill is used to crush the composite to pass through a sieve with a specified mesh size (e.g., a sieve with a mesh size in the range of 400μm to 500μm).

[0114] • Step (3): Step to obtain silicon nitride micronized powder

[0115] The coarsely pulverized silicon nitride powder is further micronized to obtain micronized silicon nitride powder. Micronization is carried out, for example, by using a micronization device such as a jet mill or a ball mill. The obtained micronized powder may also be classified as needed. Classification can be performed by sieving, wet classification, etc. It should be noted that by performing wet classification, dense silicon nitride can be obtained, thus easily yielding silicon nitride particles with a high ratio of the displacement at the point of failure to the maximum displacement in the compression test. Furthermore, by adjusting the number of classifications to an optimal range, the energy applied externally to the silicon nitride particles can be adjusted, resulting in easily obtaining silicon nitride particles with high strength at the maximum displacement in the compression test.

[0116] • Process (4): The process of obtaining silicon nitride powder

[0117] Silicon nitride micronized powder is heat-treated to obtain silicon nitride powder. Through heat treatment, an oxide film is formed on the surface of the silicon nitride particles, thus chemically stabilizing the particles. The heat treatment is carried out at atmospheric temperature between 500°C and 1200°C, preferably above 800°C and below 1100°C. The heat treatment time can be adjusted appropriately according to the heat treatment temperature. For example, the heat treatment time is 5 hours.

[0118] In the method for manufacturing silicon nitride powder, silicon nitride composite crystals are synthesized by combustion synthesis, and then crushed, graded and micronized, thereby manufacturing the silicon nitride powder involved in the embodiments of the present invention.

[0119] [Resin Composition]

[0120] The resin composition according to embodiments of the present invention comprises a resin and silicon nitride powder according to embodiments of the present invention. The resin / silicon nitride powder ratio of the resin composition according to embodiments of the present invention can be appropriately determined according to the purpose and / or use. As an example, the ratio can be 5-75% by volume of resin and 95-25% by volume of silicon nitride powder relative to the resin composition (composite).

[0121] It should be noted that the filling rate of silicon nitride powder in the resin composition refers to the content (volume%) of silicon nitride powder when the volume of the resin composition (including silicon nitride powder) is set to 100 vol%.

[0122] The method for manufacturing the resin composition is described.

[0123] A resin composition can be obtained by mixing silicon nitride powder with a resin using commonly used and known methods. For example, if the resin is in a liquid state (e.g., liquid epoxy resin), the liquid resin, silicon nitride powder, and curing agent are mixed and then cured using heat or ultraviolet light to obtain the resin composition. The curing agent, mixing method, and curing method can use known substances and methods. On the other hand, if the resin is in a solid state, the desired resin composition can be obtained by mixing silicon nitride powder with the resin and then kneading it using known methods such as melt kneading.

[0124] The resin used in the resin composition can be a known resin such as epoxy resin. The type of resin can be selected from thermoplastic resins, thermoplastic elastomers, and thermosetting resins. It should be noted that a single resin can be used, or two or more resins can be used in combination.

[0125] Furthermore, as needed, two or more known additives such as plasticizers, curing accelerators, coupling agents, fillers, pigments, flame retardants, antioxidants, surfactants, compatibilizers, weathering agents, antiblocking agents, antistatic agents, leveling agents, and release agents may be added alone or appropriately mixed into these resin compositions without impairing the effects of the present invention.

[0126] The silicon nitride powder and resin compositions comprising the silicon nitride powder according to embodiments of the present invention are particularly suitable for use as heat dissipation materials. Therefore, in one aspect of this disclosure, heat-dissipating silicon nitride powder and heat-dissipating resin compositions can be provided.

[0127] Example

[0128] Hereinafter, embodiments of the present invention will be described in detail based on examples implemented to illustrate the effects of the embodiments of the present invention. It should be noted that the embodiments of the present invention are not limited in any way by the following embodiments.

[0129] <Preparation of Silicon Nitride Powder>

[0130] Si powder (particle size = 5 μm) and separately prepared silicon nitride powder (particle size = 1 μm) as a diluent were mixed using a rotary ball mill. The amount of diluent added was 5–8% by mass relative to the total raw material (including diluent). The mixed powder was filled into a carbonaceous heat-resistant insulating container with a powder coating thickness of 1 mm–80 mm on the bottom and sides, with the raw material layer thickness greater than 100 mm and less than 150 mm. The raw material layer was then covered with a powder coating thickness of 1 mm–80 mm. A lid made of carbonaceous heat-resistant insulating material was then placed on top, and synthesis was carried out under a nitrogen atmosphere of 0.9 MPa. After synthesis, the powder was coarsely pulverized (crushed) in a mortar until it passed through a sieve with a specified mesh size. The mesh size of the sieves for each sample is shown in Table 1.

[0131] The resulting coarsely pulverized powder was further micronized using a nano-jet injector (manufactured by Aishin Nanotechnologies Co., Ltd.). Micronization was performed using a nano-jet injector of the model listed in Table 1. The resulting micronized powder was classified according to the method described in Table 1. It should be noted that a portion of the micronized powder (sample No. 2) was not classified. The D50 of the classified powder of sample No. 5 was 12.0 μm, and the D50 of the classified powder of sample No. 6 was 25.2 μm.

[0132] Then, the obtained graded powder (samples No. 1, No. 3, No. 5 and No. 6) and micronized powder (sample No. 2) were placed in an alumina crucible and heat-treated in an atmospheric atmosphere under the conditions (heat treatment temperature and heat treatment time) recorded in Table 1 using a small-scale powder programmable furnace (AsOne MMF series) to obtain silicon nitride powder (samples No. 1 to 3, 5 and 6).

[0133] [Table 1]

[0134]

[0135] Various measurements were performed on the obtained samples No.1 to 3, 5 and 6 (examples) and on the commercially available silicon nitride powder (manufactured by Aldrich, silicon nitride (predominantly β-phase, ≤10 micron primary particle size, product number 248622): hereinafter referred to as "sample No.4") as a comparative example.

[0136] (1) The ratio of the displacement d1 at the failure point to the maximum displacement d2: d1 / d2

[0137] A compression test was conducted on the silicon nitride particles in the sample (silicon nitride powder) according to JIS R 1639-5 to obtain a displacement-test force curve. The test force of this curve was converted into strength according to the following formula (2) to obtain a displacement (μm)-strength (MPa) curve.

[0138] Strength (MPa) = 2.48 × test force (N) / (π × D) 2 (2)

[0139] Here, D represents the average of the major and minor axes of the silicon nitride particles in the test subject. These major and minor axes are determined by observation using an optical microscope.

[0140] In the displacement (μm) - strength (MPa) curve, the minimum displacement with a slope of 0 and exceeding 0 is set as the failure point P1. The ratio d1 / d2 of the displacement d1 at the failure point P1 and the maximum displacement d2 (i.e. the displacement at the maximum displacement point P2) is calculated.

[0141] (2) Destructive strength s1

[0142] In the above displacement (μm) - intensity (MPa) curve, the intensity of the failure point P1 is taken as the failure intensity s1 (MPa) of the silicon nitride particles in the sample (silicon nitride powder).

[0143] (3) Apparent density

[0144] The apparent density of the sample (silicon nitride powder) was determined according to JIS R 1620:1995. The determination method and conditions are as follows.

[0145] • Measurement method: Gas displacement method

[0146] • Sample drying: 200℃ for more than 8 hours

[0147] • Device used: AccuPyc 1330 (MicroMeritics)

[0148] • Measurement conditions

[0149] Number of purging cycles: 10

[0150] Purge filling pressure: 15.0 psig

[0151] Number of measurements: 5

[0152] Filling pressure measured: 15.0 psig

[0153] Equilibrium pressure: 0.005 psig / min

[0154] Precision setting measurement: Yes

[0155] Tolerant fluctuation error: 0.05%

[0156] Sample cell size: 10cm 3

[0157] (4) β-conversion rate

[0158] The X-ray diffraction pattern of the sample (silicon nitride powder) was obtained using a powder X-ray diffraction apparatus (Rigaku Electron apparatus). The measurement conditions were set as follows.

[0159] •X-ray source: CuKα rays

[0160] •X-ray output: 45kV, 200mA

[0161] • Graphite monochromator

[0162] • Diffraction angle (2θ): Scanning in 0.02° increments across a range of 2 to 90°.

[0163] • Scanning speed: 21.7 deg / minute

[0164] When the sample contains components other than silicon nitride, the proportions of these components are determined by comparing their peaks with those of standard samples containing the same components. In samples No. 1–6, the obtained powder X-ray diffraction patterns confirmed that the samples consisted only of α-type and β-type silicon nitride. Based on this, the proportion of β-type silicon nitride (β-ratio) in the samples was calculated using the Gazzara & Messier method.

[0165] (5) L2 / L1 is the maximum particle size of silicon nitride particles below 1% (maximum particle size of single crystal particles).

[0166] Cross-sectional observation specimens were prepared using silicon nitride particles. In the preparation of these specimens, the silicon nitride particles were embedded in resin, and then the resin was cut from the silicon nitride particles using a diamond tool. A Pt protective film was then deposited onto the cross-section, and the cross-section was prepared by Ar ion milling. The specimen was then fixed to the SEM sample stage using Cu double-sided tape, and SEM-EBSD measurements were performed without deposition. The observation position was determined by ensuring that two or more silicon nitride particles were completely within the observation area (i.e., two or more silicon nitride particles did not contact the frame of the observation area). Measurements were performed using β-type silicon nitride particles.

[0167] The following equipment was used for sample pretreatment and EBSD determination.

[0168] •Use equipment

[0169] Ion milling equipment: E-3500 (manufactured by Hitachi High-Tech Corporation)

[0170] Ion sputtering equipment: E-1030 (manufactured by Hitachi, Ltd.)

[0171] Schottky scanning electron microscope: SU5000 (manufactured by Hitachi High-Tech Corporation)

[0172] Backscattered electron diffraction apparatus: Velocity (manufactured by METEK Co., Ltd.)

[0173] The conditions for EBSD determination were set as follows.

[0174] • Measurement area: 500.0 μm × 400.0 μm

[0175] • Accelerating voltage: 15.0kV

[0176] •Magnification:×500

[0177] • Vacuum degree: 30Pa

[0178] In the obtained EBSD images, select two or more silicon nitride particles that do not contact the observation area. Calculate the average length L1 of the outer edge of each silicon nitride particle using ImageJ (made by the National Institute of Health) image processing software. Additionally, calculate the total length L2 of the boundary lines. The "total length L2 of boundary lines" is the sum of all boundary lines contained within the silicon nitride particle, excluding the outer edge of the silicon nitride particle. The total length L2 of boundary lines is obtained by adding the total length of the grain boundaries within the silicon nitride particle to the total length of the inner wall of any void (if the silicon nitride particle contains voids). It should be noted that here, "grain boundary" and "boundary line" refer to boundaries in the EBSD analysis results where the crystal orientation difference (hinged angle) exceeds 15° (also known as a large-angle grain boundary).

[0179] This measurement is performed once using any 20 silicon nitride particles. Silicon nitride particles with an L2 / L1 ratio of less than 1% are considered as single-crystal particles, and their major axis length is measured as the "maximum particle size of a single crystal particle". If the 20 measured silicon nitride particles contain multiple single-crystal particles, the arithmetic mean of their maximum particle sizes is calculated.

[0180] (6) Elastic energy absorption

[0181] The area enclosed by the displacement (μm) - intensity (MPa) curve, the straight line of intensity = 0 MPa, and the straight line of displacement = d1 (the oblique part) is used as the elastic absorbed energy (MPa•μm) of the silicon nitride particles in the sample (silicon nitride powder) to calculate.

[0182] (7) Strength s2 at the maximum displacement

[0183] In the above displacement (μm) - intensity (MPa) curve, the intensity at the maximum displacement point P2 is taken as the intensity s2 (MPa) at the maximum displacement.

[0184] (8) The ratio of the breaking strength s1 to the strength s2 at the maximum displacement: s1 / s2

[0185] In the above displacement (μm) - strength (MPa) curve, calculate the ratio s1 / s2 of the strength (failure strength) s1 (MPa) at the failure point P1 and the strength s2 (MPa) at the maximum displacement point P2.

[0186] (9) Average offset of the diffraction angles corresponding to the (110), (200), (101) and (210) planes of β-type silicon nitride

[0187] In the above X-ray diffraction pattern, the diffraction angles (2θ / °) corresponding to the (110), (200), (101), and (210) (or (120)) planes of β-type silicon nitride are obtained, and are denoted as a, b, c, and d, respectively. Substitute the obtained a to d into the above equation (1) to calculate the value of the left side of the above equation (1).

[0188] (10) Thermal diffusivity of the resin composition (complex)

[0189] Epoxy resin (main agent: room temperature curing embedding resin type 53 (manufactured by Sankei Co., Ltd.) 010-8140, curing agent: room temperature curing embedding resin type 53 (manufactured by Sankei Co., Ltd.) 010-8143) and sample (silicon nitride powder) were mixed at a ratio of 50:50 (volume ratio). The mixture was stirred and mixed using a degassing mixer (manufactured by Thinky Co., Ltd.) to obtain an epoxy resin-filler (silicon nitride powder) composite. The silicon nitride powder filling rate in the resin composition was 50% by volume.

[0190] A mold frame with a 1cm × 10cm rectangular hole was fabricated on a 1mm thick aluminum plate. A PET film coated with a release agent (back side film) was attached to the back side of the mold frame, with the release agent coating side facing the mold frame, covering the rectangular hole. After injecting the stirred composite into the rectangular hole of the mold frame, a PET film coated with a release agent (surface side film) was attached from above, with the release agent coating side facing the mold frame and resin composition. Then, slight pressure was applied from above the surface side film using a metal roller to fill the rectangular hole of the mold frame with the composite. Another aluminum plate was placed on top of the surface side film, and the composite was heated at 100°C for 1 hour to cure. After curing, the plate was cooled until it reached approximately room temperature. The aluminum plate was then removed, and the surface and back side PET films were peeled off from both sides of the cured composite to obtain a sheet sample for thermal diffusivity measurement.

[0191] The thermal diffusivity of the obtained sheet-like samples was determined.

[0192] Thermal diffusivity was measured using a temperature wave thermal analysis (TWA) method at room temperature, by preparing a 10 mm long × 10 mm wide × 1 mm thick test piece from a sheet sample of the aforementioned resin composition. The ai-Phase Mobile instrument manufactured by ai-Phase Corporation was used as the measuring apparatus.

[0193] Regarding thermal diffusivity, measurements are taken at any three points on a test piece, and the average value is calculated based on the results of these three measurements.

[0194] The measurement results are summarized in Tables 2 and 3.

[0195] [Table 2]

[0196]

[0197] [Table 3]

[0198]

[0199] The measurement results will be discussed below.

[0200] Resin compositions using silicon nitride powder from samples No. 1 to 3, 5 and 6, which satisfy the requirements of Embodiment 1 and / or Embodiment 2 of the present invention, exhibit excellent thermal diffusivity. On the other hand, resin compositions using silicon nitride powder from sample No. 4, which does not satisfy the requirements of Embodiment 1 and Embodiment 2 of the present invention, exhibit poor thermal diffusivity.

[0201] This application claims priority to Japanese Patent Application No. 2023-058730, filed on March 31, 2023, which is incorporated herein by reference.

Claims

1. A silicon nitride powder comprising a plurality of silicon nitride particles, wherein the ratio of the displacement of the failure point to the maximum displacement of the silicon nitride particles in a particle compression test exceeds 0.

22.

2. The silicon nitride powder according to claim 1, wherein, The silicon nitride particles exhibit a destructive strength exceeding 727 MPa in the particle compression test.

3. A silicon nitride powder comprising a plurality of silicon nitride particles, wherein the strength of the silicon nitride particles at the maximum displacement in a particle compression test exceeds 3473 MPa.

4. The silicon nitride powder according to claim 3, wherein, The ratio of the destructive strength of the silicon nitride particles to the strength at the maximum displacement in the compression test of the particles is greater than 0.

18.

5. The silicon nitride powder according to claim 3 or 4, wherein, It satisfies the following equation (1). (|a-23.34| / 23.34+|b-27.01| / 27.01+|c-33.63| / 33.63+|d-36.02| / 36.02) / 4<0.292•••(1) In equation (1), a, b, c and d are the diffraction angles (°) corresponding to the (110), (200), (101) and (210) planes of β-type silicon nitride in the X-ray diffraction pattern with CuKα rays as the X-ray source.

6. The silicon nitride powder according to claim 1 or 3, wherein, Apparent density greater than 3.17 g / cm³ 3 .

7. The silicon nitride powder according to claim 1 or 3, wherein, The β-conversion rate is over 65%.

8. The silicon nitride powder according to claim 1 or 3, wherein, The maximum particle size of the silicon nitride particles is 6.8 μm or more, wherein the ratio of the total length L2 of the inner boundary line to the length L1 of the outer edge, L2 / L1, is less than 1%.

9. A resin composition comprising a resin and the silicon nitride powder as described in claim 1 or 3.

Citation Information

Patent Citations

  • Silicon nitride powder, silicon nitride sintered compact, and circuit board for electronic component using the sintered compact

    JP2004262756A

  • High-purity, low-aluminum spherical β-silicon nitride powder, its manufacturing method and applications

    JP2022522814A

  • Method for producing silicon nitride powder by metal reduction

    JP2022541208A

  • High-efficiency belt and method for manufacturing the same

    JP2023058730A